The Management of an Institutional Network through Relational Trust : Case Study of the EASF (East Africa Standby Force) - (:unkn) unknown (My University, 2023)
Based on the case of the East Africa Standby force (EASF), one the 5 forces making up the African Union Standby Force, and justified in view of the small number, if not non-existent, of works on the subject, this research on « the management of an institutional network through relational trust…» gives rise to this question: « does an institutional network (formalism of rules, charter of rights and duties, institution as a guardian of trust, distribution of power through elected representatives, …) function exclusively on the basis of a trust in the institutions for the members of the network, or are other trust and regulation mechanisms, that are more tacit and informal in nature, useful and necessary? ».Moreover, how does the informal dimension in the cooperation between partners (tacit conventions, habits, interpersonal trust, …) play a role in the management of an institutional network based a priori on formal partnership rules (membership charter, borders of solidarity, sharing of resources and competences, …)? How, through concertation, coordination and discussion mechanisms, does the informal complement the formal?As part of a qualitative research method, and through case studies applied to this regional defense and security organization (EASF) in the study of its management, decision-making, resource management mechanisms…, we have attempted to understand how both (informal and formal) converge in its management.We have found that in a large majority (3 cases out of 4) the informal aspect interferes in the cooperative sphere or in the regulation of the network, corroborating the finding that, to any formal structure (formal rules, formalized relationships, …) is grafted an informal part (interpersonal relationships, non-mandated links, etc.)This should be taken into account for the management of EASF, and in order to allow an evolution of theory as well, by considering that, to be efficient while respecting the members' autonomy,
Keywords: African Research